Principal’s Visionary Leadership and Work Climate toward Elementary School Teachers’ Performance - Ihsana El Khuluqo; Chidam Cholik (STAI Hubbulwathan Duri, 2022)
This research aims to reveal the influence of principal’s visionary leadership (X1) and work climate (X2) on teachers’ performance (X3). The type of research used is quantitative research. The target population in this study were all public elementary school principals and teachers in Kedaung Kaliangke Village as many as 160 people. The population is divided into 1 Village, with purposive sampling techniques. The researchers selected 12 schools consisting of 160 teachers and principals. In deciding the research sample, the Slovin formula was utilized. From the calculation, they obtained 114 people as research sample. Data collection technique used was using questionnaire with survey methods. The instruments were analyzed using the Likert model scale. The results of the study informed three main information. First, there were directly and positively influenced by 48% of Teacher Performance (X3) influenced by the second principal’s visionary leadership (X1). Second, there was a direct and positive influence of 39% performance variation (X3) influenced by the teacher working climate (X2). Third, there was a direct and positive influence of 62% variation of the working climate (X2) influenced by visionary leadership (X1). As a conclusion, there is positive correlation among the three variables, namely principal’s visionary leadership, work climate, and teacher performance.